Pneumococcal conjugate vaccine against serotype 3 pneumococcal pneumonia in adults: A systematic review and pooled analysis - McLaughlin, John M.; Jiang, Qin; Gessner, Bradford D.; Swerdlow, David L.; Sings, Heather L.; Isturiz, Raul E.; Jodar, Luis (Vaccine, 2019)
Serotype 3 pneumococcal disease has not substantially declined at the population level after the routine introduction of 13-valent pneumococcal conjugate vaccine (PCV13) into pediatric immunization programs across the globe. This epidemiological finding has generated debate regarding the effectiveness of PCV13 against serotype 3 disease. Evaluating PCV13 effectiveness against serotype 3 is especially critical in adults, where serotype 3 makes up an important amount of remaining pneumococcal disease. We performed a systematic review of the published literature to assess the direct effectiveness of PCV13 against serotype 3 community-acquired pneumonia (CAP) among adults. We then estimated overall vaccine effectiveness (VE) using a pooled analysis of the individual-level, raw data. Two published studies met inclusion criteria. One was a randomized controlled trial conducted in the Netherlands and published in 2014. The other was a recently-published case-control study conducted in Louisville, Kentucky that used a test-negative design (TND). We also identified a third TND study conducted in Argentina that was recently presented as a conference abstract but is not yet published. All three studies were conducted in adults aged ≥65 years. PCV13 VE against serotype 3 hospitalized CAP was 52.5% (95%CI: 6.2–75.9%) from the pooled analysis of individual-level data from all three studies. Results were similar if the unpublished estimate was excluded (serotype 3 VE = 53.6% [95%CI: 6.7–76.9%]). No heterogeneity was observed. Currently-available evidence, although limited to three studies, suggests that PCV13 provides direct protection against serotype 3 hospitalized CAP in adults aged ≥65 years.